2014
DOI: 10.14233/ajchem.2014.15744
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Estrogen Derivative

Abstract: Some estrogen derivatives have been developed for use in different biological and analytical methods 1-3 . For example, there are studies which show the synthesis of 2-alkylsulfanyl estrogens which are achieved by a directed ortho-lithiation reaction of suitably protected estrone followed by disulfide quench and final deprotection 4 . Other data showed the synthesis of nitrile derivatives of estrogens by reaction of 7α-cyano-19-nortestosterone with copper(II ) bromide in acetonitrile at room temperature, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Furthermore, another report display that some pyranopyrazole derivatives can act as positive inotropic agents in a spontaneously hypertensive rats model 24 . Recently was prepared a pyridine-hexacyclic-steroid derivative which produce positive inotropic activity in an isolated rat heart model 25 . All these data showed that several drugs can exert changes in the system cardiovascular; however, the molecular mechanism involved in their biological activity of each compound is very unclear; perhaps these effects are due to differences in the chemical structure of each drug or to different methods used in each experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another report display that some pyranopyrazole derivatives can act as positive inotropic agents in a spontaneously hypertensive rats model 24 . Recently was prepared a pyridine-hexacyclic-steroid derivative which produce positive inotropic activity in an isolated rat heart model 25 . All these data showed that several drugs can exert changes in the system cardiovascular; however, the molecular mechanism involved in their biological activity of each compound is very unclear; perhaps these effects are due to differences in the chemical structure of each drug or to different methods used in each experiment.…”
Section: Introductionmentioning
confidence: 99%